Synthèse d’entretien avec le kaam naaba - Tapsoba, Tatiana Nadine (Criminal justice institutions and the social trajectories of adolescents/youth in Burkina Faso: endogenous/local forms and patterns of punishment, 2021)
Following an interview with the Kaam Naaba of Manga, this report describes the types of misconduct and the procedure for dealing with them. The report also presents the respondent's perception of the notion of punishment, judgment, condemnation and punishment in relation to gender and social class. Finally, the report describes the collaboration between traditional and modern justice, as well as the popular perception of prison as a model of punishment.
Keywords: Administration of Justice; Teenagers; Youth; Punishment; Kaam Naaba